Power and Class Conflict in Bullet Train (2022): A Marxist Analysis - Aluyani Rose Titania Putri Lature; Irma Rahmawati (PT. Alahyan Publisher Sukabumi, 2026)
This research examines the representation of power relations and class conflict in the film Bullet Train (2022) directed by David Leitch by applying a Marxist perspective. The purposes of this research are to analyze how power is portrayed among the characters and to identify how class conflict is represented in the film. This research uses a qualitative descriptive method. The data are collected from scenes, dialogues, character actions, and visual elements in the film. The data are analyzed using Marxist theory, particularly concepts of bourgeoisie and proletariat, exploitation, hegemony, alienation, and class struggle. The results of this research show that power in Bullet Train is dominated by characters who control capital and organizational structures, particularly the White Death, who represents the bourgeois class. Meanwhile, characters such as Ladybug and other assassins represent the proletariat who sell their labor and operate under systems they do not control. Class conflict is represented through fragmented and individualized struggles among the working-class characters, where competition replaces solidarity. The train functions as a metaphor for capitalist society, symbolizing confinement, hierarchy, and continuous conflict driven by capital. This research concludes that Bullet Train is not only an action-comedy film, but also a cultural text that reflects capitalist power structures and ongoing class conflict in contemporary society.